2003
DOI: 10.1253/circj.67.617
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcome of Percutaneous Transluminal Coronary Rotational Atherectomy in Patients With End-Stage Renal Disease

Abstract: The clinical results of percutaneous transluminal coronary rotational atherectomy (PTCRA) in dialysis patients were retrospectively evaluated in comparison with coronary artery bypass grafting (CABG). From 1997 to 2001, 44 consecutive dialysis patients with 61 lesions underwent PTCRA and 55 consecutive dialysis patients underwent CABG. The initial success rate of PTCRA was 98%. The PTCRA group had a shorter hospital stay (13+/-17 vs 60+/-35 days, p=0.0001) and a lower rate of complications (11% vs 42%, p=0.001… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 31 publications
2
23
0
Order By: Relevance
“…Four studies included patients who underwent repeat revascularization, a larger proportion (22%) of patients in two studies (31,33), and a small proportion (11%) in the remaining 2 studies (25,32). Two of the studies included a small number of patients (13%) who had emergent surgeries (30,32). The weighted mean age of patients was 60 yr, and most relevant characteristics like hyperlipidemia, ejection fraction, hypertension, and diabetes mellitus were similar among those receiving CABG and PCI.…”
Section: Patient Characteristics and Outcome Definitionsmentioning
confidence: 99%
See 4 more Smart Citations
“…Four studies included patients who underwent repeat revascularization, a larger proportion (22%) of patients in two studies (31,33), and a small proportion (11%) in the remaining 2 studies (25,32). Two of the studies included a small number of patients (13%) who had emergent surgeries (30,32). The weighted mean age of patients was 60 yr, and most relevant characteristics like hyperlipidemia, ejection fraction, hypertension, and diabetes mellitus were similar among those receiving CABG and PCI.…”
Section: Patient Characteristics and Outcome Definitionsmentioning
confidence: 99%
“…A cardiac event was defined as a composite outcome of myocardial infarction or need for repeat revascularization in nine studies. (20,22,(25)(26)(27)(28)31,32,35) Eight studies also reported events of myocardial infarction on their own (20,25-27,30 -32,35).…”
Section: Patient Characteristics and Outcome Definitionsmentioning
confidence: 99%
See 3 more Smart Citations